METAFORA KONSEPTUAL DALAM LAGU KARYA SEKAI NO OWARI - Muhammad Alif Alfatih; Arza Aibonotika; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: According to Lakoff and Johnson (2003: 10-32), metaphor is something that has another meaning and its main function is to understand, in other words, metaphor is part of figurative language that compares one thing to another. Lakoff and Jhonson (1987: 453) explain image scheme is a repetitive structure in cognitive processes that forms patterns of understanding and reasoning. Since childhood, humans have begun to decompose an entity into several characteristics, then the information is stored and converted into a simple symbol. This study aims to explain the types of conceptual metaphors and image schemes contained in the song sekai no owari.The theory used is conceptual metaphor theory from Lakoff and Johnson and image schema theory from Lakoff and Johnson. This research is a qualitative descriptive study. Of the 14 songs used as objects in this study, 47 were successfully analyzed and found 5 data of structural metaphors, 22 data of orientational metaphors, 11 data of ontological metaphors, and 9 data of ontological metaphors with personification subtypes.Keywords: Metafora, Skema Citra.